THE INFLUENCE OF STORE ATMOSPHERE, BRAND IMAGE, AND PRICE ON PURCHASE DECISIONS AT BINGXUE CABANG AMPLAS. - Mhd Rasyid Siddiq; Anggia Sari Lubis; Toni Hidayat; Muhammad Rahmat (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
The research aims to determine and analyze the influence of store atmosphere, brand image, and price on purchasing decisions at Bingxue Cabang Amplas. The method used in this research is quantitative. The population in this research consists of consumers who made purchases at Bingxue Cabang Amplas from March to July, totaling 577 consumers. The sample was taken using the Slovin formula, resulting in a total of 85 consumers as respondents who made purchases at Bingxue Cabang Amplas. The data collection technique in this research employed random sampling based on observation data, interviews, and questionnaires using a Likert scale for data measurement. The data analysis techniques included validity tests, reliability tests, and classical assumption tests. The data analysis method used was multiple linear regression with the help of the SPSS program. The results of this research show that, partially, store atmosphere has a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. Simultaneously, store atmosphere, brand image, and price have a significant effect on purchasing decisions at Bingxue Cabang Amplas, with an Fcount value (5.836) > Ftable (2.716), and a significance value of 0.001 < 0.05.